Determinants of Social Entrepreneurial Intentions - Hockerts, Kai (Entrepreneurship Theory and Practice, 2017)
This article tests the model proposed by Mair and Noboa (2006) who identify four antecedents which they suggest predict social entrepreneurial intentions. The study extends the model by including prior experience with social problems as an additional variable. Findings show that prior experience predicts social entrepreneurial intentions. This effect is mediated by the antecedents suggested by Mair and Noboa. Social entrepreneurial self–efficacy has both the largest impact on intentions as well as being itself most responsive to prior experience. Lastly, the study shows that the amount of optional social entrepreneurship electives students enroll in is predicted by social entrepreneurial intentions.